2015
DOI: 10.1590/1414-431x20154221
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of methicillin resistance and PVL genes among Staphylococcus aureus isolates from the nares and skin lesions of pediatric patients with atopic dermatitis

Abstract: Staphylococcus aureus is highly prevalent among patients with atopic dermatitis (AD), and this pathogen may trigger and aggravate AD lesions. The aim of this study was to determine the prevalence of S. aureus in the nares of pediatric subjects and verify the phenotypic and molecular characteristics of the isolates in pediatric patients with AD. Isolates were tested for antimicrobial susceptibility, SCCmectyping, and Panton-Valentine Leukocidin (PVL) genes. Lineages were determined by pulsed-field gel electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 33 publications
9
26
0
Order By: Relevance
“…This lineage carrier of PVL genes had already been reported in Argentina (Egea et al, 2014;Fernandez et al, 2012) and in Brazil (Cavalcante et al, 2015;Caboclo et al, 2013;Schuenck et al, 2012). Moreover, in the present study, a VISA isolate belonging to USA1100/ST30 was identified, indicating the relevance of this lineage among the PVL-positive MRSA isolates.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…This lineage carrier of PVL genes had already been reported in Argentina (Egea et al, 2014;Fernandez et al, 2012) and in Brazil (Cavalcante et al, 2015;Caboclo et al, 2013;Schuenck et al, 2012). Moreover, in the present study, a VISA isolate belonging to USA1100/ST30 was identified, indicating the relevance of this lineage among the PVL-positive MRSA isolates.…”
supporting
confidence: 82%
“…Furthermore, analysis of a collection of bacterial isolates having a common characteristic, such as PVL genes, can help to understand the relationship between them. However, in general, available studies demonstrate only the occurrence of these isolates (Nichol et al, 2013;Cavalcante et al, 2015;Caboclo et al, 2013;Egea et al, 2014;Fernandez et al, 2012;Schuenck et al, 2012). In the present study, we analyzed a collection of 50 PVL-positive S. aureus isolates obtained in a 6-year period in Rio de Janeiro hospitals as their phenotypic and molecular characteristics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 This bacterial overgrowth, with subsequent biofilm formation and mainly related to the pathogenic strains of Staphylococcus aureus (methicillin-resistant Staphylococcus aureus), would be directly related to changes in the cutaneous barrier. 51,52,53 Cutaneous microbiota is associated with dermatitis severity, but it is less clear its effect in the pathogenesis; antibiotic interventions are also expected to be able to improve the dermatitis symptom scores. However, a systematic review, 54 in 21 studies with different interventions (oral antibiotics, antibacterial soaps, topical steroids/antibiotics/antifungal, baths with antibacterial solutions) did not show differences statistically significant.…”
Section: Does the Cutaneous Microbiota Influence The Control Of Atopimentioning
confidence: 99%
“…Molecular characterization of S. aureus isolates may be achieved by, for example, pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) [4,5]. Most of the S.aureus isolates recovered from AD children belong to well-established lineages of different geographical regions, such as USA1100/ST30, USA400/ST1 and USA800/ST5 in Brazil [6,7] and ST188 in Korea [8].…”
mentioning
confidence: 99%